Respuesta :

The answer is actually choice A

---------------------------------------------------------
---------------------------------------------------------

If we add up the equations straight down we will have 0a+2b = 6

Note how adding the 'a' terms gives us 3a + (-3a) = 3a-3a = 0a. The 0a term is really 0 since 0 times anything is 0. So the 'a' terms will go away

The equation 0a+2b = 6 turns into 0+2b = 6 and that simplifies to 2b = 6

To isolate b, we divide both sides by 2

2b = 6
2b/2 = 6/2
b = 3

We can stop here since only one answer choice has b = 3, which is choice A. However, let's keep going to find the value of 'a'

Plug b = 3 into any equation with 'a' and 'b', then solve for 'a'

3a+4b = 9
3a+4*3 = 9
3a+12 = 9
3a+12-12 = 9-12
3a = -3
3a/3 = -3/3
a = -1

So a = -1 and b = 3 pair up to form (a,b) = (-1,3)

--------------------------------------

To check, plug this ordered pair back into both equations

Equation 1:
3a+4b = 9
3*(-1)+4*3 = 9
-3+12 = 9
9 = 9
Equation 1 has been checked out

Equation 2:
-3a-2b = -3
-3(-1)-2(3) = -3
3 - 6 = -3
-3 = -3
this is true as well

So this confirms that the final answer is choice A

Answer:

A. (-1,3)

Step-by-step explanation:

If we add up the equations straight down we will have 0a+2b = 6

Note how adding the 'a' terms gives us 3a + (-3a) = 3a-3a = 0a. The 0a term is really 0 since 0 times anything is 0. So the 'a' terms will go away

The equation 0a+2b = 6 turns into 0+2b = 6 and that simplifies to 2b = 6

To isolate b, we divide both sides by 2

2b = 6

2b/2 = 6/2

b = 3

We can stop here since only one answer choice has b = 3, which is choice A. However, let's keep going to find the value of 'a'

Plug b = 3 into any equation with 'a' and 'b', then solve for 'a'

3a+4b = 9

3a+4*3 = 9

3a+12 = 9

3a+12-12 = 9-12

3a = -3

3a/3 = -3/3

a = -1

So a = -1 and b = 3 pair up to form (a,b) = (-1,3)

To check, plug this ordered pair back into both equations

Equation 1:

3a+4b = 9

3*(-1)+4*3 = 9

-3+12 = 9

9 = 9

Equation 1 has been checked out

Equation 2:

-3a-2b = -3

-3(-1)-2(3) = -3

3 - 6 = -3

-3 = -3

this is true as well

So the final answer is choice A